Site-dependent doping effects on quantum transport in zigzag graphene nanoribbons. (November 2015) - Pi, Shu-Ting; Dou, Kun-Peng; Tang, Chi-Shung; Kaun, Chao-Cheng
Abstract: We investigate the site-dependent effects of a substitutional nitrogen or boron atom on quantum transport in zigzag graphene nanoribbons from first principles and tight-binding model calculations. The former show three characteristics in transmission spectra: drops around the Fermi level, dips at the bottom of the second conduction (nitrogen) or valence (boron) band, and sharp peaks at the Fermi level. Comparing with the latter, the origins of the transmission features are revealed. The drops are attributed to the impurity onsite potential or its Coulomb interaction, depending on its location. The dips come from the interaction between the impurity and its neighbor atoms. The peaks are associated with the resonant long-rang components of the Coulomb interaction.